ACCUMULATION OF SUBSEQUENT ALTERNATIVE CLAIMS - Salma, Marija (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
The paper examines rules governing accumulation of subsequent alternative claims in domestic and foreign procedural literature. We have pointed out that subsequent alternative claims are not genuine alternative claims since the court decides on secondary claim only after rejecting primary claim. Consequently, subsequent alternative claims are not equal as they are in the case of genuine accumulation of claims, because the court decides only on one claim, either on primary claim or on secondary, alternative claim. In case of subsequent alternative claims the subsequent alternative claim depends on the primary claim and if the primary claim is granted, the court shall not decide on the subsequent, secondary claim. The claimant decides on the order in which the court shall decide upon the claims as it is within the claimant’s disposition.